Socio-Economic Situation In The Turkestan Region At The End Of The 19th And Early 20th Centuries - Buriev, Zavkiddin; Ibodillayeva Farzona, Gaybullayev Javohir, Muhammadov Firdavs (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
The population resettled in Turkestan faced a number of problems in the process of getting used to the new conditions of the place. Among these problems, the issue of difficulties in moving from the reception centers to new places and settling there is of particular importance.